2017
DOI: 10.3390/ijms18071253
|View full text |Cite
|
Sign up to set email alerts
|

Colonization and Maize Growth Promotion Induced by Phosphate Solubilizing Bacterial Isolates

Abstract: Phosphorus (P) limits the production of maize, one of the major food crops in China. Phosphate-solubilizing bacteria (PSB) have the capacity to solubilize phosphate complexes into plant absorbable and utilizable forms by the process of acidification, chelation, and exchange reactions. In this study, six bacteria, including one Paenibacillus sp. B1 strain, four Pseudomonas sp. strains (B10, B14, SX1, and SX2) and one Sphingobium sp. SX14 strain, were those isolated from the maize rhizosphere and identified base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
25
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(30 citation statements)
references
References 71 publications
3
25
1
1
Order By: Relevance
“…The ability of PGPR strains B1 and BJ-18 to form close associations with plant roots, as established with observation of GFP-tagged constructs (Li et al, 2017(Li et al, , 2019a, could explain the synergy reported herein. Endophytes interact closely with plant hosts and readily exert beneficial traits (Santoyo et al, 2016).…”
supporting
confidence: 61%
See 2 more Smart Citations
“…The ability of PGPR strains B1 and BJ-18 to form close associations with plant roots, as established with observation of GFP-tagged constructs (Li et al, 2017(Li et al, , 2019a, could explain the synergy reported herein. Endophytes interact closely with plant hosts and readily exert beneficial traits (Santoyo et al, 2016).…”
supporting
confidence: 61%
“…Paenibacillus sp. B1 (accession number: KY111475), isolated from the maize rhizosphere, is a novel species with P solubilizing ability and produce IAA (Li et al, 2017). P. beijingensis BJ-18 and Paenibacillus sp.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tested strains were evaluated for their potential to promote plant growth on wheat cultivar Jimai 22 (Shandong Runfeng Seed Industry Co., Ltd., Shandong Sheng, China), cucumber Zhongnong 8 (Beijing Shengfeng Garden Agricultural Technology Co., Ltd., Beijing, China) and tomato Jiafen 15 (Tianjin Xingke Seed Co., Ltd., Tianjin, China) seedlings in the greenhouse of China Agricultural University, Beijing, China. The lengths and dry weights of three plants inoculated with strains were determined by the procedure described by Li et al (2017).…”
Section: Methodsmentioning
confidence: 99%
“…Given these advantages, PGPR are widely used in sustainable agriculture to promote plant growth and control fungal pathogens (Verma et al, 2018). Some of Paenibacillus species can influence plant growth by one or more of mechanisms mentioned above (Li et al, 2017; Weselowski et al, 2016; Xie et al, 2016). Nowadays, with the rapid growth of population, most regions have increased the cereals production by the overuse of fertilizers, which not only accounts for a larger percentage of farmers’ expenses but also increase risks of negative effect on environment (Curatti & Rubio, 2014; Ivleva et al, 2016; Tayefeh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%